PENGHITUNGAN VALUE AT RISK (VAR) PORTOFOLIO OPTIMUM SAHAM PERUSAHAAN BERBASIS SYARIAH DENGAN PENDEKATAN EXPONENTIALLY WEIGHTED MOVING AVERAGE (EWMA) (STUDI KASUS PADA PERUSAHAAN YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX PERIODE JUNI 2016-NOVEMBER 2017) - Raudhatul Fadilah; Noor Shodiq Askandar; Anik Malikah (e_Jurnal Ilmiah Riset Akuntansi, 2018)
ABSTRACTThis research was conducted with the aim of assessing the maximum potentialloss that might occur to investors if they invest in sharia-based public shares. Themethod used in this study is Value at Risk (VaR) with an Exponentially WeightedMoving Average (EWMA) approach. The sample in this study were 24 stock thatwere consistently registered in Jakarta Islamic Index (JII) period June 2016 -November 2017. After calculating the optimum stock portfolio formation, 11 stockwere include in the optimum portfolio category.The result of this study indicate that the optimum portfolio obtained consistsof SSMS 16,6%; LPKR 15,9%; TLKM 12,03%; WIKA 12,02%; PGAS 11,9%;WSKT 10,6%; SMRA 7,6%; UNTR 6,4%; UNVR 2,9%; ICBP 2,4%; and AALI1,2%. Value at Risk (VaR) with an Exponentially Weighted Moving Average(EWMA) approach fluctuates (not constant) for 1 day, 5 days, and 10 days. Thisis because the return obtained for each day is different so that the risk faced arealso different where it will also affect the maximum risk that might occur on theday.Keyword: Value at Risk (VaR), Exponentially Weighted Moving Average (EWMA)